Perfectionism and Eating Disorder Tendencies In Calorie-Tracking App Users - Sabina, Talitha Sahda; Geshica, Lavenda (Faculty of Psychology, Universitas Gadjah Mada, 2025)
While diet and calorie-counting mobile applications can support users in achieving their goals, studies have also highlighted their potential negative impact on eating disorder tendencies. This study examines perfectionism as a possible contributing factor to such tendencies among users of calorie-counting apps. Data were collected over 21 days through voluntary participation, yielding a sample of 83 individuals aged 18–39. Participants completed online self-report questionnaires, including the Indonesian Multidimensional Perfectionism Scale (IMPS) and the Eating Attitudes Test (EAT-26). Results from simple linear regression analysis indicated that higher levels of perfectionism were strongly associated with an increased likelihood of engaging in behaviours linked to eating disorders (β = 0.62, p < .001), with perfectionism emerging as a substantial predictor of these behaviours (R² = 0.38). These findings underscore the need for further research on the psychological impact of calorie-tracking apps and suggest the importance of incorporating design strategies that promote healthier user experiences.